2011
DOI: 10.1038/nrd3502
|View full text |Cite
|
Sign up to set email alerts
|

Beyond classical benzodiazepines: novel therapeutic potential of GABAA receptor subtypes

Abstract: GABAA receptors are a family of ligand-gated ion channels which are essential for the regulation of central nervous system function. Benzodiazepines – which target GABAA receptors containing the α1, α2, α3, or α5 subunits non-selectively – have been in clinical use for decades and are still among the most widely prescribed drugs for the treatment of insomnia and anxiety disorders. However, their use is limited by side effects and the risk of drug dependence. In the past decade, the identification of separable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
637
0
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 618 publications
(661 citation statements)
references
References 107 publications
15
637
0
9
Order By: Relevance
“…Both animal research and clinical studies have established that perturbation of the GABA inhibitory system is involved in the pathogenesis of a variety of neurological diseases, including epilepsy, schizophrenia, depression, anxiety and chronic pain. [31][32][33] Most of these previous studies focused on the post-synaptic GABA A receptor of GABA synapses as potential therapeutic targets for the treatment of these pathological conditions. However, given the activity-dependent GAD65 function and particularly, activity-regulated Gad2 expression through epigenetic control of transcription, Gad2 might play a more important role in the chronic disease condition-induced plasticity of central GABA synapses.…”
Section: Gad2 and Gaba-related Neurological Diseasesmentioning
confidence: 99%
“…Both animal research and clinical studies have established that perturbation of the GABA inhibitory system is involved in the pathogenesis of a variety of neurological diseases, including epilepsy, schizophrenia, depression, anxiety and chronic pain. [31][32][33] Most of these previous studies focused on the post-synaptic GABA A receptor of GABA synapses as potential therapeutic targets for the treatment of these pathological conditions. However, given the activity-dependent GAD65 function and particularly, activity-regulated Gad2 expression through epigenetic control of transcription, Gad2 might play a more important role in the chronic disease condition-induced plasticity of central GABA synapses.…”
Section: Gad2 and Gaba-related Neurological Diseasesmentioning
confidence: 99%
“…Benzodiazepines potentiate the effects of the neurotransmitter g-aminobutyric acid (GABA) via positive allosteric modulation at the g-aminobutyric acid type A (GABA A ) receptor. GABA A receptors are heteropentameric chloride ion channels assembled in a typical stoichiometry of 2 a, 2 b, and 1 g subunits; conventional benzodiazepines bind to GABA A receptors containing a1, a2, a3, or a5 subunits (a1GABA A , a2GABA A , a3GABA A , or a5GABA A receptors, respectively; Rudolph and Knoflach, 2011;Tan et al, 2011). Previous studies have shown localization of a1GABA A receptors on inhibitory interneurons that synapse with DA neurons in the ventral tegmental area (VTA; Heikkinen et al, 2009;Tan et al, 2010) while a3GABA A receptors are expressed at lower levels on the DA neurons themselves (Fritschy and Mohler, 1995;Ciccarelli et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Etomidate binds to sites in the transmembrane region of the receptor where it modulates GABA A R efficacy levels at low concentrations and directly activates at high concentrations, similarly to the barbiturate type of modulators at this receptor (12,13). In contrast, benzodiazepines only modulate the GABA potency and are known to bind in an extracellular pocket in the receptor ␣-␥ interface, a pocket that is structurally similar to the GABA-binding ␤-␣-subunit pocket (6,9).…”
mentioning
confidence: 99%
“…Both receptor types are implicated as either cause or remedy in devastating diseases, including anxiety, Parkinson, and Alzheimer diseases, pain, and attention deficit hyperactivity disorder (3)(4)(5). Therefore, the development of drugs that target these receptors is a priority area for research (3,6). Although allosteric modulators are mechanistically less well understood than agonists, they are believed to have advantages as pharmaceuticals.…”
mentioning
confidence: 99%